Comment: The Emotional Basis of Toxic Affect. (January 2018) - Fischer, Agneta H.
I focus on some differences between negative emotional states and how they are coped with in explaining different cardiac risks. The different cognitive, motivational, and physiological characteristics of emotions imply different appraisals of the negative event, and different resources to cope with the event. Cardiovascular activity depends on these different appraisals and coping strategies. For example, cortisol levels have shown to be differently associated with anger and fear responses to social stress. In addition, different ways to regulate one's emotions are also associated with different bodily responses that may increase or decrease cardiac risks. Future research should not only examine different emotions to stressors, but also more long-term regulation strategies and coping resources, such as self-esteem.